The development status of Sunpower DS 10 cryocooler. Issue 1 (1st May 2022) - Kim, Yongsu; Collins, Josh
Abstract: The CryoTel® MT is an integral Stirling cryocooler with 5 W of lift capacity at 77 K with a nominal input power of 80 W. The MT has the smallest size and cooling capacity among Sunpower's integral cryocoolers. The contact-free operation of the moving components by using Sunpower's gas bearings technology results in a long lifetime of the cooler, achieving an MTTF of over 200, 000 hrs. Followed by the design and product development efforts of the CryoTel DS 30, Sunpower has been developing another dual opposed piston and split configuration Stirling cryocooler, DS 10, by leveraging the back end of the MT cryocooler. By using as many as existing components and subassemblies from the MT cryocooler, we minimized new component design and development for the wave generator. The cold head is entirely new, but it is a scale-down design of the DS 30 cold head. Relying on the experience and lessons learned from the DS 30, we expect minimal design, development, and troubleshooting efforts in production. The development of the DS 10 wave generator complete and tested with a DS 30 cold head. The test showed 11.8 W of lift at 77 K with an input power of 160 W.